Tribology of Diamond-Like Carbon Films
DOI: 10.1007/978-0-387-49891-1_8
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Superlubricity in Diamond-like Carbon Films

Abstract: Diamond-like carbon (DLC) films have emerged as a class of very important tribological materials in recent years mainly because of their outstanding properties, such as high mechanical strength and hardness, excellent chemical inertness, and exceptional friction and wear performance under both dry and lubricated sliding conditions. Persistent and systematic research efforts during the last decade have resulted in the development of a new breed of DLC films providing superlubricity and near-wearless sliding eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
(174 reference statements)
0
18
0
Order By: Relevance
“…Hence, the thermochemical calculations of reaction products between hemisphere materials and metal dopant were able to predict whether or not a transfer film would bond. These calculations, along with in situ observations, can also account for the relatively high friction coefficients that Erdemir et al [21] found during run-in of hydrogenated DLC coating against an Al 2 O 3 ball; there too, the transfer film did not adhere readily to Al 2 O 3 resulting in a longer high friction run-in period than with a steel ball.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hence, the thermochemical calculations of reaction products between hemisphere materials and metal dopant were able to predict whether or not a transfer film would bond. These calculations, along with in situ observations, can also account for the relatively high friction coefficients that Erdemir et al [21] found during run-in of hydrogenated DLC coating against an Al 2 O 3 ball; there too, the transfer film did not adhere readily to Al 2 O 3 resulting in a longer high friction run-in period than with a steel ball.…”
Section: Discussionmentioning
confidence: 86%
“…Fontaine et al [19,20], in studies of the friction behavior of steel pins sliding against DLC coatings in UHV and backfill gases, provided evidence that both the environment and chemistry of the surface of the stationery slider affect the adhesion of the transfer film and friction behavior. Similarly, Erdemir et al [21] investigated the friction coefficient of a hydrogenated DLC coating against DLC coated, steel, and ceramic pins. They inferred that the relatively high friction coefficients with ceramic pins during run-in might have been due to the difficulty of forming a continuous transfer film, a process that accompanied the rapid drop in the friction coefficient obtained with steel pins.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of a-C, the third-body material does not agglomerate in the center and it is concentrated in an external ring, out of the contact region, surrounded by many loose debris particles. The formation of a tribolayer helps to accommodate the sliding motion, decreasing shear forces at the contact as happened in many solid lubricant systems (DLC, MoS 2 , and MeC/a-C) [4,65,66]. The softer a-C:Ag films contribute to the transfer of material to the ball counterface in much extent and the presence of metallic silver can help to promote its adhesion to the steel ball [31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The triboplasma acts beneficially to reduce friction by forming high-molecular-weight products in organic gas atmosphere under dry sliding [4] or harmfully to decompose the lubricating oil molecules under oil lubrication [5]. The triboplasma is possibly the origin of the inexplicable phenomena and problems such as ultra-low friction [6,7], superlubricity [8] or abnormal wear [9], chemical change of the stable lubricants [5] and so on. Some of these could be solved [5] and explained [9] by the action of the rear outside triboplasma.…”
Section: Introductionmentioning
confidence: 99%